Home visits in brain tumor patient: how nurse and family members cooperate in tumor patient’s family self-care - Lang, Liwei; Yan, Zhiyue; Tang, Hailiang (Chinese Journal of Cancer Research, 2013)
Purposes: We reported the roles and functions of nurses in home visits for brain tumor patients using the family health assessment guide in the study. Methods: One patient of brain glioma was chosen as the case illustration. The nurses assessed the patients’ situation, their families and living environment individually. All these factors were analyzed together. Results: The nurses then implemented their knowledge and skills to adopt different measures in different conditions, investigated the patients’ health problems and carried out personalized effective actions. Conclusions: Nurses should put effort into community nursing to allow patients to live in a safe environment, to satisfy the health needs of human being and their needs for health knowledge, and enhance their self-care abilities.